Tailoring Recruitment and Outreach Strategies for Underrepresented Students in Public Health Pipeline Programs. (December 2021) - Caldwell, Cleopatra Howard; Thomas, Dana; Hoelscher, Hannah; Williams, Hallie; Mason, Zachary; Valerio-Shewmaker, Melissa A.; Panapasa, Sela V.
Studies have shown that racial and ethnic minority health professionals are more likely than those in the majority to work in predominantly underserved, largely minority communities. Increasing the pool of underrepresented racial and ethnic professionals could help reduce health disparities. Summer programs giving minority students public health training and experiences can increase the number who enter the health professions. This article describes recruitment strategies for obtaining a diverse pool of applicants for such a program as part of a Centers for Disease Control and Prevention funded multisite undergraduate training program intended to increase the diversity of the public health workforce. The recruitment strategies used included institutional linkages, collaborative partnerships, and interpersonal contacts. No one strategy was more effective; however, Hispanic/Latinas were more likely to be recruited through institutional linkages, but less likely to be recruited through interpersonal contacts than other female groups. Understanding successful recruitment strategies to achieve a diverse application pool for public health training programs is vital to achieve health equity.